Integrated redox-active reagents for photoinduced regio- and stereoselective fluorocarboborylation - Weigang Zhang (Nature Portfolio, 2020)
The synthesis of vinylboronates and alkylboronates often suffers from step-tedious and poorly stereoselective procedures. Here, the authors report a bench-stable redox-active reagent for the radical difunctionalization of alkenes and alkynes affording fluorine-containing vinylboronates and alkylboronates.